2020
DOI: 10.1371/journal.pgen.1008689
|View full text |Cite
|
Sign up to set email alerts
|

A Rad51-independent pathway promotes single-strand template repair in gene editing

Abstract: The Rad51/RecA family of recombinases perform a critical function in typical repair of double-strand breaks (DSBs): strand invasion of a resected DSB end into a homologous double-stranded DNA (dsDNA) template sequence to initiate repair. However, repair of a DSB using single stranded DNA (ssDNA) as a template, a common method of CRISPR/Cas9-mediated gene editing, is Rad51-independent. We have analyzed the genetic requirements for these Rad51-independent events in Saccharomyces cerevisiae … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 91 publications
1
24
0
Order By: Relevance
“…Strikingly, across each of these donors, genes encoding components of the MutSα/MutLα DNA mismatch repair (MMR) complexes ( MSH2 , MSH6 , MLH1 , and PMS2 ) strongly promoted some scarless SSTR outcomes while suppressing others, with the suppressed set biased for outcomes missing SNVs from the 3’ ends of ssODNs (Figure S7C-S7E). These results are consistent with observations from previous studies, which proposed that MMR activity installs SNVs encoded on the 3’ ends of ssODNs by “fixing” mismatches established upon donor annealing 78, 81, 82 .…”
Section: Resultssupporting
confidence: 93%
“…Strikingly, across each of these donors, genes encoding components of the MutSα/MutLα DNA mismatch repair (MMR) complexes ( MSH2 , MSH6 , MLH1 , and PMS2 ) strongly promoted some scarless SSTR outcomes while suppressing others, with the suppressed set biased for outcomes missing SNVs from the 3’ ends of ssODNs (Figure S7C-S7E). These results are consistent with observations from previous studies, which proposed that MMR activity installs SNVs encoded on the 3’ ends of ssODNs by “fixing” mismatches established upon donor annealing 78, 81, 82 .…”
Section: Resultssupporting
confidence: 93%
“…Previous studies using I-SceI breaks have shown that single-strand templated repair (SSTR) is Rad51-independent in yeast ( 32 ). A recent publication also supports a Rad51-independent mechanism for SSTR after Cas9 breaks, and has found that SSTR is dependent on Rad52, Rad59, Srs2 and the Mre11-Rad50-Xrs2 (MRX) complex in yeast ( 33 ). Similarly, a CRISPR screen for SSTR suggests no involvement of RAD51 and BRCA2 in ssODN integration ( 34 ).…”
Section: Resultsmentioning
confidence: 83%
“…However, we surmise that the remaining examined colonies were also edited by homology-directed mechanisms, since we have not recovered any spontaneous herbicide-resistant mutant in any of our negative control experiments ( Supplemental Table S3 ). As described in other eukaryotes ( Gallagher and Haber, 2018 ; Paix et al, 2017 ; Boel et al, 2018 ; Gallagher et al, 2020 ), we expected that Cas9-induced DSBs in Chlamydomonas would be repaired by the single-strand template repair (SSTR) mechanism (see “Discussion”). Following this model ( Supplemental Figure S4 ), the PPX1 ssODN would be used as a homologous template for DNA synthesis primed by the 3′ ending strand on the left side of the cleavage site.…”
Section: Resultsmentioning
confidence: 91%
“…DSB repair by error-prone nonhomologous end-joining (NHEJ), including canonical and alternative pathways, may result in insertions/deletions (i.e. indels) and/or missense/nonsense mutations at the target sites ( Rodgers and McVey, 2016 ; Gallagher and Haber, 2018 ; Scully et al, 2019 ; Capdeville et al, 2020 ; Gallagher et al, 2020 ). Alternatively, homology directed repair (HDR) in the presence of template donor DNA, which can also occur by several pathways, may result in precise sequence changes ( Rodgers and McVey, 2016 ; Gallagher and Haber, 2018 ; Paix et al, 2017 ; Scully et al, 2019 ; Capdeville et al, 2020 ; Gallagher et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%